2017
DOI: 10.1080/17550874.2017.1287785
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and clonal diversity in introduced populations ofMimulus guttatusassessed by genotyping at 62 single nucleotide polymorphism loci

Abstract: Background: Single nucleotide polymorphisms (SNPs) are increasingly being used to study non-native populations. SNPs are relatively information poor on a per locus basis, but allow genotyping more loci than others markers (e.g., microsatellites) and have the advantage of consistent allele calls between studies.  Aims: We investigated the utility of a newly developed set of SNP markers, suitable for high throughput genotyping to characterise genotypic variation and population structure in non-native populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…The seeds were sampled from a herbarium specimen collected by the US National Park Service for the University of Alaska Museum Herbarium (ALA; ALAAC accession V142998). Although this specific population has not been previously analysed using genetic markers, our work suggests that Alaskan populations are genetically close to British material [18]. Individuals from this Alaskan population grown in controlled environment facilities produce many long stolons.…”
Section: Materials and Methods (A) Plant Materialsmentioning
confidence: 70%
See 1 more Smart Citation
“…The seeds were sampled from a herbarium specimen collected by the US National Park Service for the University of Alaska Museum Herbarium (ALA; ALAAC accession V142998). Although this specific population has not been previously analysed using genetic markers, our work suggests that Alaskan populations are genetically close to British material [18]. Individuals from this Alaskan population grown in controlled environment facilities produce many long stolons.…”
Section: Materials and Methods (A) Plant Materialsmentioning
confidence: 70%
“…The history of invasion of M. guttatus is best documented in the UK, where it was introduced in 1812, and became naturalized by the 1830s [17]. Although the exact source-of-origin of UK M. guttatus is unknown, genetic analyses suggest that it was introduced from the north Pacific, and historical records suggest that it may have originated in Alaska [17,18]. Admixture between native and introduced populations from the UK and New Zealand of M. guttatus has been shown to result in heterosis in the probability of flowering, flower number, clone size and biomass in a previous glasshouse study [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast genome (cpDNA) plays an important role in plants because it contains essential genes for performing photosynthesis (Sugiura, 1992). Additionally, the highly conserved of cpDNA among plants resulted in the useful applications of cpDNA data in reconstructing phylogeny, exploring biogeography, surveying population genetics, and developing molecular markers (Cui et al, 2017; Fischer et al, 2017; Leaché & Oaks, 2017; Pantoja et al, 2017). In Poaceae, different studies on cpDNA have been reported (Matsuoka et al, 2002; Hand et al, 2013; Zhang et al, 2016; Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sexual reproduction, M. guttatus can also have vigorous clonal reproduction, particularly in habitats that remain permanently wet (van Kleunen, ). By analysing 62 SNP markers in 14 populations of M. guttatus , Pantoja, Simón‐Porcar, Puzey, and Vallejo‐Marín () found that reproductive strategies of M. guttatus in its invaded range in the United Kingdom vary from mostly clonal to mostly sexual. Clonal reproduction might allow M. guttatus to rapidly colonize a new habitat, after long‐distance dispersal of its small seeds (Truscott et al., ).…”
Section: Discussionmentioning
confidence: 99%